G447 The cross-sectional and longitudinal assessment of the effects of nursery attendance and breastfeeding on respiratory symptoms and their impact on quality of life in the first 22 months of life- results from the liverpool baby breathing study. (12th March 2018) - Stead, J; Semple, M; Griffith, B; Pickles, R; Patel, S; Barclay, J
Abstract : Aims: To determine the effects of breastfeeding and nursery attendance on respiratory symptoms and quality of life related to respiratory symptoms in infants from Liverpool over the first 22 months of life. Methods: The Liverpool Baby Breathing Study (LBBS) uses a parent completed respiratory symptom questionnaire, to assess respiratory symptoms in infants from four to twenty-two months of age. Infants were recruited from the Liverpool Women's Hospital between 23/01/2013 and 03/11/2014. Questionnaires were sent to participants at four, ten, sixteen and twenty-two months of age via post or an automated emailing system. The cross-sectional analysis of the LBBS was weighted to ensure the cohort's index of multiple deprivations was comparable to the eligible births. χ2, Mann-Whitney U and Fisher's Exact Test were used to compare questionnaire scores and symptom prevalence between those who were breastfed and attended nursery and those who were not. The longitudinal analysis of the LBBS was performed using multi-level mixed effects models. Results: At four, ten and sixteen months of age infants who were breastfed had a lower symptom scores and a smaller prevalence of a variety of respiratory symptoms than those who were not. Some of these findings showed a dose-response relationship. This relationship was no longer present at twenty-two months of age. Longitudinally, breastfeeding was shown to reduce symptom scores over the first twenty-two months of life. At four months infants who attended nursery had a higher prevalence of snoring and were more likely to attend the GP with respiratory symptoms. At ten, sixteen and twenty-two months of life nursery attenders had higher symptom scores and a higher prevalence of various respiratory symptoms than non-attendees. Longitudinally over time, nursery attendance increased symptom scores over the first twenty-two months of life. Nursery attendance reduced the quality of life of both the infant and their families due to respiratory symptoms at ten and sixteen months of age. Conclusion: Breastfeeding was protective of respiratory symptoms over the first 22 months of life. Contrastingly, nursery attendance increased respiratory symptoms and reduced the quality of life of both infants and their family over the first 22 months of life.